Active and passive drag: the role of trunk incline - Zamparo, P.; Gatta, G.; Pendergast, D.; Capelli, C. (European Journal of Applied Physiology, 2009)
The aim of this study was to investigate the role of trunk incline (TI) and projected frontal area (A eff) in determining drag during active/passive measurements. Active drag (D a) was measured in competitive swimmers at speeds from 0.6 to 1.4 m/s; speed specific drag (D a/v 2 ) was found to decrease as a function of v (P < 0.001) to indicate that the human body becomes more streamlined with increasing speed. Indeed, both A eff and TI were found to decrease with v (P < 0.001) whereas C d (the drag coefficient) was found to be unaffected by v. These data suggest that speed specific drag depend essentially on A eff. Additional data indicate that A eff is larger during front crawl swimming than during passive towing (0.4 vs. 0.24 m2). This suggest that D a/v 2 is larger than D p/v 2 and, at a given speed, that D a is larger than D p.